Real-time thermo-optical analysis of polymer samples by quantitative polarized optical microscopy - Bicalho, Luciana Assumpção (2017)
An experimental setup using a polarized optical microscope fitted with a detection module capable of measuring the cross-polarized transmitted light intensity and the transmitted light intensity of the polymer sample being analyzed, together with an accompanying calculation procedure, is proposed in order to characterize in real-time thermal transitions and degree of crystallinity, as well as birefringence (which is a measure of orientation) and turbidity. The experimental assessment of the technique was carried out studying commercial poly(ethylene terephthalate) multifilaments with different crystallinity and stretching levels and by direct comparison with the features of conventional DSC curves obtained under similar experimental conditions. While an excellent correlation was found between the type and temperature ranges of thermal events as detected by thermal and optical techniques, the measured birefringence was shown to be sensitive to distinct filament stretching levels, but unaffected by geometrical factors. Contrarily, turbidity is influenced by the latter